Taking the wrong road in the capital/revenue enquiry: the controversial case of the share incentive trust - Esat, Intikab-Alam (Centre for Law and Society, 2026)
It is sometimes said that taxation is the price we pay for civilisation. 1 What is perhaps not said as often is that not every citizen or organisation pays taxes, nor are many of them, and justifiably at that, obliged to do so. The share incentive trust, according to the highest court of the land, is one such organisation. After a chequered, controversial, and sometimes protagonistic seven-year history, the Appellate Division of the Supreme Court, in C.I.R. vs Pick 'N Pay Employee Share Purchase Trust2 ruled, by a majority of 3-2, that share incentive trusts, as presently structured, are not liable for normal income tax on profits made through dealing in its founder company's shares. The Rise of the Share Incentive Trust During the boom years of the stock exchange in the late 1960's, the idea of providing a tax-free employment fringe benefit for corporate employees by the use of stock option plans gained widespread popularity. 3 Key management staff were granted options to purchase shares in their employer company exercisable in the future (subject to continued employment) at the market value prevailing on the date the options had been granted.